Inconsistencioa juridica en el Codigo de la Niñez y la Adolescencia, respecto a la no reclamación de la alimentos y la sucesión para solicitarlo en favor del menor - Mogrovejo Salcedo, Pablo Andres (2016)
The modern law constitutionalism neo-focused, maintains order, defense, security and application of principles, even more so when we are in a constitutional rule of law and social justice, the importance and the contemporary socio own legal right correlation, synthesize my studio to one of the priority groups, such as children and adolescents, who are protected by the State, the agencies from the public, private and family; and for a set of existing provisions in the law objective, binding constitutional rights and alimony as a necessity for the harmonious development of good living. The importance lies as the reference group, according to a principle of best interests, also constitutionally established that the State, society and the family as a priority promote the comprehensive development in all aspects. For the foregoing reasons my work is focused to the study of those parents who take possession of the child, who lacks the financial resources to meet the development of good living, personal subjective matters not claim before the competent judicial authority, making possible my proposal for guarantee the rights of the child, that this product does not infringe no claim nor leave it in the lowest economic legally indefensible.